Scaffolding and reading comprehension: a literature review - Zhang, Huiling; Swaran Singh, Charanjit Kaur (Universiti Teknologi MARA, 2025)
This literature review critically examined the role of scaffolding in enhancing reading comprehension among English as a Foreign Language and English as a Second Language learners. Grounded in Vygotskian theory, which posited that scaffolding provides temporary support enabling learners to perform tasks beyond their current capabilities, the review aimed to synthesise findings from 17 past studies. The guiding research questions included: What are the relevant past studies related to scaffolding and reading comprehension? What were the interventions used? What insights can be drawn from the results? Methodologically, this review involved a rigorous selection process, with studies chosen from the Scopus database based on their citation rankings and relevance. The findings revealed a diversity of scaffolding techniques, including technological scaffolding, collaborative learning, assessment-based interventions, and cognitive/metacognitive strategies. While most studies reported positive outcomes, such as improved reading comprehension and reduced learning anxiety, the effectiveness of these interventions was often influenced by contextual factors like learner characteristics and task complexity. The discussion emphasised the need for future research to optimise scaffolding techniques, particularly in technology-enhanced environments. This review contributed to the existing literature by offering educators and researchers a comprehensive reference for understanding the impact of scaffolding on reading comprehension. It underscored the importance of context-sensitive, adaptable scaffolding strategies to meet the evolving needs of learners in diverse educational settings. Future recommendations include exploring innovative scaffolding techniques and refining existing methods to enhance their efficacy across different learning environments.